Triangular Microstrip Antenna for Circularly-Polarized Synthetic Aperture Radar Sensor Application - Muhammad Fauzan Edy Purnomo; Akio Kitagawa (Institute of Advanced Engineering and Science, 2018)
In this paper, we obtain the basic construction of triangular microstrip antennas based on the analysis of the single patch and array two patches. This construction use the basic corporate feeding-line with modified lossless T-junction power divider for Circularly Polarized-Synthetic Aperture Radar (CP-SAR) sensor embedded on airspace with compact, small, and simple configuration. The design of Circular Polarization (CP) is realized by truncating the whole three tips and adjusted the parameters of antennas at the resonant frequency, f = 1.25 GHz. The equations for reciprocal, lossless, and matched of the modified lossless T-junction power divider are also described. The result of characteristic performance and S-parameter for the single patch both Left-Hand Circular Polarization (LHCP) and Right-Hand Circular Polarization (RHCP) at the resonant frequency show consecutively 7.15 dBic and 7.16 dBic of gain, 0.12 dB and 0.11 dB of axial ratio, -26.75 dB and -26.72 dB of S-parameter. For array two patches, the result of gain, axial ratio, and S-parameter both of LHCP and RHCP are 7.63 dBic, 7.62 dBic, 2.68 dB, 2.74 dB, -19.43 dB, and -19.40 dB, respectively. The modified lossless T-junction power divider both for LHCP and RHCP are capable of being reciprocal, matched, and lossless at all ports.